Pemberdayaan Kelompok Tani dalam Pembuatan Probio_Fm sebagai Bahan Fermentasi Pakan Ternak di Bangka Tengah - Rufti Puji Astuti; . Yulia (Institut Pertanian Bogor, 2019)
Beef cattle farming is the mainstay of Nadi Lestari Farmer Group in Perlang Village.The challenges faced by these farmers include the expensive cost of procuring cattle feed, little effect of concentrate feed on cattle productivity, farmers low proficiency in technology, high production cost due to dependence on commercial bio_activator, and environmental pollution. The purpose of this community service is to equip the farmers in this area with the knowledge on how to produce probio_Fm and process feed. The method used in this study includes preparation, socialization of the procedure of making probio_Fm, demonstration of the procedure, application of probio_Fm in feed processing, tutoring and monitoring and evaluation.The data were collected by means of interviews and questionnaires. Qualitative descriptive analysis was used to analyze the data. As a result of the community empowerment program, the farmers gained the skill to make probio_Fm and are more creative feed processing.The achievement score of the lesson material for 20 farmers is 75%.The farmers were considered creative, since probio_Fm was applied in the processing of green feed or concentrate feed. Probio_Fm-based feeding positively affected the livestock’s appetite, feed management became easier and time and cost efficient, and the environmental pollution decreased. The results of the extension showed that there were some problems in the delivery of starter materials, the characteristics of local raw materials, and the supply of electricity. The results of monitoring and evaluation suggest that the farmers are now committed to using probio_Fm.The farmers in Nadi Lestari group are assumed to be able to produce, use, and, develop probio_Fm sustainably.